2009
DOI: 10.1016/j.ejso.2009.02.013
|View full text |Cite
|
Sign up to set email alerts
|

HER-family gene amplification and expression in resected pancreatic cancer

Abstract: Aims: Despite surgical resection, pancreatic cancer carries a poor prognosis. In search for new molecular therapeutic targets, we investigated the expression of the HER-family and gene amplification of HER-2 in pancreatic adenocarcinomas of different stages.Methods: Tissue of 45 resected patients was analysed for all HER-family 1-4 expression by immunohistochemistry and HER-2 gene amplification was assessed by multiplex ligation-dependent probe amplification and chromogenic in situ hybridization. The type of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 42 publications
(30 reference statements)
1
22
1
1
Order By: Relevance
“…These observations are consistent with the findings of Friess et al [7]and Vaidya et al [8]. However, Kawesha et al [9] and Velde et al [10] found that HER3 overexpression is not a prognostic indicator for pancreatic cancer. The cause of these conflicting results is unclear, but the discrepancy may be due to differences in the methods of immunohistochemical evaluation used by different investigators.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…These observations are consistent with the findings of Friess et al [7]and Vaidya et al [8]. However, Kawesha et al [9] and Velde et al [10] found that HER3 overexpression is not a prognostic indicator for pancreatic cancer. The cause of these conflicting results is unclear, but the discrepancy may be due to differences in the methods of immunohistochemical evaluation used by different investigators.…”
Section: Discussionsupporting
confidence: 83%
“…The cause of these conflicting results is unclear, but the discrepancy may be due to differences in the methods of immunohistochemical evaluation used by different investigators. Specifically, Friess et al [7 ]defined HER3-positive staining as strong membranous and/or cytoplasmic staining in at least 10% of cancer cells, Vaidya et al [8 ]classified tumors as positive if they had focal or diffuse staining with a score of at least 2+ using a 4-point (0 to 3+) scoring scale, Kawesha et al [9 ]defined tumors as positive if there was unequivocal cytoplasmic staining in more than 5% of cancer cells, and Velde et al [10 ]also only examined cytoplasmic staining and used the same criteria as Vaidya et al [8]. We used the same semiquantitative evaluation method and definition of HER3-positive staining as Vaidya et al [8]and Velde et al [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could easily be attributed to the small size of the patient population, although two significant factors should be considered. The first is that these biomarkers had almost exclusively been previously studied by immunohistochemistry (1,(11)(12)(13)(22)(23)(24), and not mRNA expression. The second is that most of the factors had never been studied in patients treated with EGFR inhibitors (1,(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%